2008
DOI: 10.1007/s00442-008-1006-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen preferences and plant-soil feedbacks as influenced by neighbors in the alpine tundra

Abstract: Plant resource partitioning of chemical forms of nitrogen (N) may be an important factor promoting species coexistence in N-limited ecosystems. Since the microbial community regulates N-form transformations, plant partitioning of N may be related to plant-soil feedbacks. We conducted a (15)N tracer addition experiment to study the ability of two alpine plant species, Acomastylis rossii and Deschampsia caespitosa, to partition organic and inorganic forms of N. The species are codominant and associated with stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 80 publications
4
39
0
Order By: Relevance
“…The results have indicated that the presence of neighbors changes plants' resource use traits Liancourt et al, 2013). Yet, relatively few studies have assessed how N acquisition (e.g., uptake of 15 NH 4 + or 15 NO 3 À ) is influenced by interactions with neighbors using stable N isotope analysis, which has proven to be a powerful tool for gaining insight into the foraging strategy of roots (Ashton et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The results have indicated that the presence of neighbors changes plants' resource use traits Liancourt et al, 2013). Yet, relatively few studies have assessed how N acquisition (e.g., uptake of 15 NH 4 + or 15 NO 3 À ) is influenced by interactions with neighbors using stable N isotope analysis, which has proven to be a powerful tool for gaining insight into the foraging strategy of roots (Ashton et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Results from 15 Nlabeling with different N forms suggested that N allocation strategies play an important role (Kahmen et al 2006) or that N partitioning may allow for niche separation among subordinate plant species (McKane et al 2002;Aanderud & Bledsoe 2009;von Felten et al 2009). Moreover, recent studies indicated neighbour-identity effects on plant species capacity to take up different N forms or enhance the uptake of particular N forms (Miller, Bowman & Suding 2007;Ashton et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, plant d 15 N values reflected a community-wide switch between two mineral N sources along a precipitation gradient in Hawaii (Houlton et al 2006;Schuur and Matson 2001) and among spatially distinct N sources in litter and mineral soils of French Guiana (Schimann et al 2008). Experimental additions of 15 N-enriched tracers have shown that plants prefer mineral over organic forms of N, even in N limited ecosystems (Harrison et al 2007;Ashton et al 2008), and that local adaptations to growth conditions in part determine N uptake rates and preferences for ammonium versus nitrate (Wang and Macko 2011;Andersen and Turner 2013).…”
mentioning
confidence: 99%